ETNOPEDAGOGI DALAM LINGKUNGAN PENDIDIKAN MASYARAKAT: ANALISIS KOMPARATIF KI HADJAR DEWANTARA DAN TRADISI PANSORI KOREA - Kim, Daemin; Karwati, Uus; Haerani, Reni (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2025)
The 21st-century educational paradigm, which tends to be functionalist, often overlooks aspects of character building and communal responsibility. This study responds to these limitations by exploring the 'Community Education Environment' through a comparative study between Ki Hadjar Dewantara's Ethnopedagogy and the Korean Pansori tradition, as well as Indonesian oral literature. The main objective is to reconstruct a 'Community-Based Learning' model sourced from Asian local wisdom for application in modern education. Using a structural-semiotic approach, this research analyzes the homology between the philosophy of the 'Three Centers of Education' (Tripusat Pendidikan) and Dewantara's three leadership principles (Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani) with the interactive dynamics of Pansori elements (Sorikkun, Gosu, Chuimsae). Specifically, the analysis of the Simcheongga text and the Sundanese epic Mundinglaya Di Kusumah proves that traditional narratives are not merely entertainment but high-level non-formal educational platforms that transmit moral values and social norms. The study also examines the media transition from simple orality to literacy through the case of Wawacan to provide insights for developing educational content in the digital era. The results confirm that traditional arts contain prototypes of participatory learning relevant to addressing the dehumanization of education. It is concluded that a society's cultural assets are vital 'Social Capital' to complement the modern school system and foster learners into complete human beings.